2009
DOI: 10.1111/j.1532-5415.2009.02181.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin‐Resistant Staphylococcus aureus Colonization in Residents and Staff in Nursing Homes in Northern Ireland

Abstract: OBJECTIVES: To determine the prevalence of, and factors associated with, methicillin‐resistant Staphylococcus aureus (MRSA) colonization in residents and staff in nursing homes in one geographically defined health administration area of Northern Ireland. DESIGN: Point prevalence study. SETTING: Nursing homes. PARTICIPANTS: Residents and staff in nursing homes. MEASUREMENTS: Nasal swabs were taken from all consenting residents and staff. If relevant, residents also provided urine samples, and swabs were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 49 publications
7
46
3
Order By: Relevance
“…The MRSA prevalence we observed was lower than in MRSA surveys in recent years in the US [41][42][43][44][45], China [46], the UK [16], France [20], Ireland [15], and Italy [24], but higher than in the Netherlands and Sweden [14,22] (Table 3). …”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The MRSA prevalence we observed was lower than in MRSA surveys in recent years in the US [41][42][43][44][45], China [46], the UK [16], France [20], Ireland [15], and Italy [24], but higher than in the Netherlands and Sweden [14,22] (Table 3). …”
Section: Discussioncontrasting
confidence: 66%
“…MDRO are regarded as a potentially serious threat to elderly people living in long-term care facilities (LTCFs). Although various studies on the prevalence of MRSA in LTCFs in Germany [7][8][9][10][11][12][13] and other European countries [14][15][16][17][18][19][20][21][22][23][24][25] have been published (< 1% in the Netherlands and Sweden, > 20% in Ireland and the United Kingdom (UK)), studies on the prevalence of MRGN such as extended-spectrum betalactamase (ESBL)-producing Enterobacteriaceae and vancomycin-resistant enterococci (VRE) among nursing home residents in German and in European LTCFs are scarce [7,14,24,26,27]. Although an increasing trend in the occurrence of ESBL-producing Enterobacteriaceae and even CRO is found in hospitals all over Europe [1,3,28,29], a lack of knowledge on multidrug-resistant organisms (MDRO) in nursing homes has to be stated.…”
Section: Introductionmentioning
confidence: 99%
“…Both MRSA prevalence in residents and care workers in our study are clearly lower than other reported by Baldwin et al, In this study the prevalence of MRSA carriers among residents was 23.3% and 7.5% in HCWs [27].…”
Section: Discussioncontrasting
confidence: 73%
“…In these areas, the proportion of invasive MRSA versus invasive MSSA may be as high as one in every two laboratory samples [6], and the parallel proportion of colonization-related MRSA versus colonization-related MSSA as high as one in every four isolates [15].…”
Section: Comments On Resultsmentioning
confidence: 99%